Factors Affecting Job Satisfaction Among Nurses in the Inpatient Unit of RS Tk. III 04.06.03 Dr. R. Soetarto Yogyakarta - Andra Purwanto Yogatama Putra; Sumijatun; Nurcahyo Andarusito (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Nurse job satisfaction is an important factor that affects service quality, organizational commitment, and workforce retention in hospitals. A decrease in the level of job satisfaction of nurses can cause burnout, high turnover, and reduce the quality of health services. This study aims to find out the factors that affect the job satisfaction of nurses in the Inpatient Unit of Tk. III Hospital 04.06.03 dr. R. Soetarto Yogyakarta. This study uses a quantitative analytical approach with questionnaire instruments distributed to 80 implementing nurses who meet the inclusion criteria, such as working actively in inpatient units, having a minimum working period of 6 months, and willing to fill out a complete questionnaire. The results showed that the variables of leadership, work environment, and compensation all had a significant effect on nurses' job satisfaction. Of these three factors, compensation has proven to be the most dominant factor in determining the level of job satisfaction of nurses. Based on these findings, it can be concluded that fair and adequate compensation is the main determinant of job satisfaction, followed by a conducive work environment and effective leadership. Therefore, hospital management needs to prioritize improving a better compensation system, accompanied by improvements in terms of leadership and quality of the work environment to improve nurses' overall job satisfaction.